Warmbread and honey cake : an inspiring collection of international recipes for the home baker - Pagrach-Chandra, Gaitiri (United Kingdom : Pavilion Books, 2009)
A comprehensive and unparalleled collection of breads, cakes and pastries from around the world, this beautiful sourcebook of recipes is also a well-researched exploration of home baking techniques and global ethnic history.
Flat breads -- Yeast breads, cakes & rolls -- Cakes & cake-making -- Small cakes, pastries & savouries -- Leaf & thread pastries --
Includes bibliographical references and index.
Keywords: BAKING